2016
DOI: 10.1016/j.watres.2016.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying bioreactor clogging potential during wastewater treatment

Abstract: Chemoheterotrophic denitrification technologies using woodchips as a solid carbon source (i.e., woodchip bioreactors) have been widely trialed for treatment of diffuse-source agricultural nitrogen pollution. There is growing interest in the use of this simple, relatively low-cost biological wastewater treatment option in waters with relatively higher total suspended solids (TSS) and chemical oxygen demand (COD) such as aquaculture wastewater. This work: (1) evaluated hydraulic retention time (HRT) impacts on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…One approach to remove nitrates from waste waters are denitrifying woodchip bioreactors, which are typically trenches filled with woody substrate, that have been successfully applied to treat tile drainage for more than twenty years (Schipper et al, 2010;Christianson et al, 2012, Addy et al, 2016. Laboratory and pilot-scale studies have demonstrated that woodchip bioreactors may be applied to treat effluents from freshwater RAS (Lepine et al, 2016;von Ahnen et al, 2016 a,b;Christianson et al, 2016;Christianson et al, 2018). These previous studies have focused on examining factors regulating woodchip bioreactor operation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to remove nitrates from waste waters are denitrifying woodchip bioreactors, which are typically trenches filled with woody substrate, that have been successfully applied to treat tile drainage for more than twenty years (Schipper et al, 2010;Christianson et al, 2012, Addy et al, 2016. Laboratory and pilot-scale studies have demonstrated that woodchip bioreactors may be applied to treat effluents from freshwater RAS (Lepine et al, 2016;von Ahnen et al, 2016 a,b;Christianson et al, 2016;Christianson et al, 2018). These previous studies have focused on examining factors regulating woodchip bioreactor operation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…hydraulic retention time Lepine et al, 2016), the possibilities to increase N removal rates (von Ahnen et al, 2016a), start-up phase at pilot-scale (von Ahnen et al, 2016b), as well as potential operational risks (e.g. bioreactor clogging Christianson et al, 2016), or mitigation of potential phosphorus leaching after bioreactor start-up (Sharrer et al, 2016;Christianson et al, 2017). Recently, woodchip bioreactors have been successfully implemented in full-scale at three commercial recirculated freshwater trout farms in Denmark (von Ahnen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms/bioslimes often form in woodchip bioreactors when too much readily available carbon is added. Formation of biofilms/bioslimes is a problem because it can clog the bioreactor pipes and reduce the flow (Gibert et al 2008; Christianson et al 2016; Husk et al 2017). Our results also suggest that DNRA bacteria can be also enriched in bioslimes, which is not desirable for nitrate removal since the DNRA process preserves N in the environment rather than releasing it as N 2 gas.…”
Section: Discussionmentioning
confidence: 99%
“…A potential solution to this problem is biostimulation, in which readily available carbon is supplemented to the woodchip bioreactor to enhance microbial denitrification rates under low temperatures (Roser et al 2018). However, addition of excess carbon could cause overgrowth of bacteria and formation of thick biofilms (bioslimes) in the bioreactor itself, or in the piping, resulting in clogging (Gibert et al 2008; Christianson et al 2016; Husk et al 2017). It is unknown whether these commonly found biofilms are composed of denitrifying micro‐organisms or what role they play in denitrifying woodchip bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…4a vs. 4b) but lower than the European Union wastewater treatment plant discharge criterion of 125 mg COD L -1 (EU, 1991). Christianson et al (2016) reported that woodchip COD flushing in pilot-scale bioreactors treating aquaculture wastewater required between 45 and 80 cumulative pore volumes, although this could be as short as approximately 20 cumulative pore volumes depending on the retention time, wood type, and pollutant of concern (Healy et al, 2012). Von Ahnen et al 2016documented that initial outflow concentrations of 647 mg COD L -1 from a willow (genus Salix) bioreactor were reduced by 90% after two days and were similar to the inflow concentrations within two weeks (estimated ~15 and ~100 cumulative pore volumes, respectively, based on a 12.5 m 3 reactor and 2.5 m 3 h -1 flow rate).…”
Section: Leachate Chemistry In Lab Testsmentioning
confidence: 99%